2006
DOI: 10.1158/0008-5472.can-05-3018
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mammalian Target of Rapamycin Signaling Pathway Contributes to Tumor Cell Survival in Anaplastic Lymphoma Kinase–Positive Anaplastic Large Cell Lymphoma

Abstract: Anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALCL) frequently carries the t(2;5)(p23;q35) resulting in aberrant expression of chimeric nucleophosmin-ALK. Previously, nucleophosmin-ALK has been shown to activate phosphatidylinositol 3-kinase (PI3K) and its downstream effector, the serine/threonine kinase AKT. In this study, we hypothesized that the mammalian target of rapamycin (mTOR) pathway, which functions downstream of AKT, mediates the oncogenic effects of activated PI3K/AKT in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 42 publications
9
174
0
4
Order By: Relevance
“…Many primary systemic ALK-positive ALCLs express the NPM-ALK fusion protein, and this protein can elicit multiple signaling pathways, which are responsible for both cell transformation and maintenance of the neoplastic phenotype [19]. Of these signaling pathways, the Ras-extracellular signal-regulated kinase (ERK) pathway primarily takes charge of translating the downstream effectors, mTOR and its target proteins for ALCL proliferation [20][21][22]. The phosphatidylinositol 3-kinase (PI3K)-Akt pathway also accounts for the small role for the ALCL proliferation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many primary systemic ALK-positive ALCLs express the NPM-ALK fusion protein, and this protein can elicit multiple signaling pathways, which are responsible for both cell transformation and maintenance of the neoplastic phenotype [19]. Of these signaling pathways, the Ras-extracellular signal-regulated kinase (ERK) pathway primarily takes charge of translating the downstream effectors, mTOR and its target proteins for ALCL proliferation [20][21][22]. The phosphatidylinositol 3-kinase (PI3K)-Akt pathway also accounts for the small role for the ALCL proliferation [22].…”
Section: Discussionmentioning
confidence: 99%
“…As we have found, the MEK/ERK pathway activates mTOR in ALK þ TCL cells and it does so more strongly than PI3K/Akt. A recent study (Vega et al, 2006) identified mTOR activation in ALK þ TCL and implicated Akt in the process. Our findings not only demonstrate that mTOR activation is triggered by NPM/ALK and that nutrients are required as the second signal for the mTOR activation in the ALK þ TCL cells but also, as discussed above, indicate that the contribution of PI3K/Akt to mTOR activation is relatively limited in such cells, in particular when compared with the MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…16 Briefly, tissue sections were subjected to deparafinization, hydration and heat-induced epitope retrieval in pH 6.0 citrate buffer (Dako, Carpinteria, CA, USA) in a steam humidifier for 30 min, followed by gradual cooling for 20 min. Endogenous peroxidase reaction was blocked by 3% H 2 O 2 solution for 10 min.…”
Section: Methodsmentioning
confidence: 99%